The EFFECT OF UNDERSTANDING LEVEL, READINESS LEVEL, AND PERCEPTION OF EASY ON THE IMPLEMENTATION OF SMALL AND MEDIUM MICRO ENTITY ACCOUNTING STANDARDS: Case Study on MSME Actors in Bandung City - Rima Melati Ramlan; Muhammad Iqbal Alamsyah (Universitas Indonesia Membangun, 2022)
This study examined the relationship between understanding level, readiness level, and perception of easiness to implementation of Financial Accounting Standards of Micro, Small, and Medium Enterprises on Micro, Small, and Medium Enterprises in the city of Bandung. The subjects in this study were 98 units of MSMEs registered at the Department of Cooperatives and MSMEs in Bandung. The method used in this study is a quantitative method with a descriptive and verification approach. To measure the classical assumption test, multiple linear regression analysis, and the coefficient of determination along with hypothesis test with SPSS for Windows version 23. The results indicate that there was a positive effect between understanding level and perception of easiness to implementation of Financial Accounting Standards of MSMEs and there is no effect between readiness level to implementation of Financial Accounting Standards of MSMEs on MSMEs in the city of Bandung. These three variables of the study gave an effective contribution as much as 19,9% while the rest came from other factors.